Analisis Hasil Tes Angket Minat dan Bakat Terhadap Pemilihan Jurusan di Sekolah Menengah Atas (SMA) - Abdillah Azmaanajidi; Habbil Qusairy; Arya Dwi Putra; Syach Alif Laziale; Wiwi Putri Zebua; Nuramalia Insani (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Education is an important thing for the life of a nation, especially its society and citizens. At the Senior High School (SMA) stage, students are faced with significant decisions regarding the choice of majors that will affect their further education. Therefore, choosing the right and suitable major is very important to ensure that students can develop their potential and interests to the maximum. Objective: The purpose of this study is to determine the direction of students' interests and talents in order to have an understanding of the choice of majors in Senior High School (SMA). The subject of this study is one person's data based on the title of the article. Case studies and group discussions are data collection methods. Qualitative data analysis is the first step in this research. The results of the research study indicate that the research subjects have good intelligence components. The results of the subject's assessment are "enough" and "good", which shows this. This study shows that the interest and talent questionnaire test conducted greatly influences the subject's choice of major that he will choose later at the Senior High School (SMA) level.